Method for one-pot conversion of PET in pure water phase system, catalyst and catalyst preparation method thereof

By using mesoporous carbon-based ruthenium oxide multifunctional catalyst in a pure aqueous phase system, PET is converted into terephthalic acid and hydrogen-rich synthesis gas in one pot, the problems of many by-products and high energy consumption in the thermochemical conversion of PET are solved, and an efficient and clean PET conversion process is achieved.

CN116143603BActive Publication Date: 2025-04-01ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211363234.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2025-04-01
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

In the prior art, the thermochemical conversion of PET has problems such as many by-products, low target product selectivity and high energy consumption. The strong alkali/strong acid catalyst used in the traditional PET hydrolysis process will cause reactor corrosion and wastewater generation, increasing the difficulty of recycling of ethylene glycol.

Method used

Under the pure aqueous phase system, a mesoporous carbon-ruthenium zinc oxide multifunctional catalyst supported by ruthenium and zinc oxide is used to convert PET into terephthalic acid and hydrogen-rich synthesis gas in one pot. By catalyzing the hydrolysis of PET and the in-situ reforming of ethylene glycol, efficient and clean conversion is achieved.

Benefits of technology

The conversion rate of PET is achieved with a high purity of terephthalic acid produced, and the mole fraction of hydrogen in the hydrogen-rich synthesis gas can reach 70%. There is no need to use acid/base/organic solvents. The process is gentle, the reaction temperature does not exceed 250℃, and no by-products such as tar are produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116143603B_ABST
    Figure CN116143603B_ABST
Patent Text Reader

Abstract

The present invention proposes a method for one-pot conversion of PET under a pure water phase system, a catalyst thereof, and a catalyst preparation method, wherein the catalyst is a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst, and the loading amount of ruthenium accounts for 1-6% of the catalyst mass; the loading amount of zinc oxide accounts for 3-20% of the catalyst mass. The catalyst preparation process is simple, the catalytic activity is high, the reusability is strong, and a conversion rate of PET close to 100% can be achieved. Among them, the method for one-pot conversion of PET is: in an environment without any acid / base / organic solvent, under the catalytic action of a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst, PET is converted into hydrogen-rich synthesis gas and terephthalic acid chemicals in a pure water phase. The process can realize efficient and clean conversion of PET, and the terephthalic acid produced has high purity, is an important chemical synthesis raw material, can be directly recycled and reused, and the hydrogen-rich synthesis gas produced is of great significance to alleviating the shortage of fossil energy.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the technical field of thermochemical catalytic conversion of waste plastics, in particular to a method for one-pot conversion of PET in a pure water phase system, a catalyst thereof and a method for preparing the catalyst. [Background technology]

[0002] The rapid development of global industry has accelerated the consumption of plastic materials, resulting in the generation of a large amount of plastic waste, posing severe challenges to the treatment and management of waste plastics. It is estimated that by 2050, the world will generate a total of 12 billion tons of waste plastics. However, most of the current waste plastic disposal is mainly landfill and incineration, and the actual recycling rate is only 9%. Polyethylene terephthalate (PET) is an important and widely used polyester plastic material. Traditional PET mechanical recycling will cause the quality of plastic products to deteriorate. Therefore, converting plastic waste into high-value fuels and materials can significantly improve the utilization rate of plastic waste.

[0003] In recent years, a series of PET thermochemical conversion technologies such as high-temperature gasification, pyrolysis, and pyrolysis-reforming have been widely studied and developed. However, the large number of by-products, low target product selectivity, and high energy consumption have greatly restricted the development of these technologies. In contrast, the reaction conditions of chemical depolymerization methods such as hydrolysis, alcoholysis, glycolysis, and aminolysis are milder. As a typical polyester plastic, the simplest method is to depolymerize PET into ethylene glycol and terephthalic acid monomers by hydrolysis of ester bonds. At present, the strong base / strong acid catalysts commonly used in the PET hydrolysis process will cause reactor corrosion and easily produce a large amount of wastewater. At the same time, the presence of impurities will increase the difficulty of recovering ethylene glycol. Therefore, the use of acid / base in the PET hydrolysis process should be avoided as much as possible.

[0004] As an important oxygen-containing hydrocarbon organic matter, ethylene glycol can be converted into hydrogen through a series of processes such as liquid phase reforming, electrocatalytic reforming, and photocatalytic reforming. However, new technical processes such as ethylene glycol electrocatalysis and photocatalytic hydrogen production are carried out independently of the PET hydrolysis process, which will increase the process complexity of future industrial applications. As an important thermochemical hydrogen production technology, the process parameters of ethylene glycol liquid phase reforming hydrogen production are basically the same as the reaction conditions of the PET hydrolysis process. Therefore, by preparing a new catalyst, coupling the PET hydrolysis technology and ethylene glycol liquid phase reforming technology in the same reaction system, converting PET into hydrogen fuel and high-value chemicals in a pure water phase will greatly simplify the industrial process and broaden the prospects for the recycling and conversion of PET plastic waste. [Summary of the invention]

[0005] The purpose of the present invention is to solve the problems in the prior art and to provide a method for one-pot conversion of PET in a pure water phase system and a catalyst and a method for preparing the catalyst. The catalyst has good recycling performance and high catalytic activity, and the preparation process is simple and easy to operate. The catalyst can be used to realize one-step efficient and clean conversion of PET in a pure water phase into hydrogen-rich synthesis gas and terephthalic acid, and the PET conversion rate is close to 100%.

[0006] To achieve the above object, the present invention proposes a method for one-pot conversion of PET in a pure water phase system, wherein pure water, PET and a catalyst are mixed in a certain proportion in the absence of acid / alkali / organic solvent, and PET is converted in one pot under a low temperature, low pressure and mild hydrothermal environment to obtain terephthalic acid chemicals and hydrogen-rich synthesis gas, wherein the catalyst is a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst loaded with ruthenium and zinc oxide. The main components of the hydrogen-rich synthesis gas include hydrogen, carbon dioxide and methane, wherein the molar fraction of hydrogen can be as high as 70%, and the PET conversion rate is close to 100%.

[0007] Preferably, the loading amount of ruthenium in the catalyst accounts for 1-6% of the mass of the catalyst, and the loading amount of zinc oxide in the catalyst accounts for 3-20% of the mass of the catalyst. The catalyst plays multiple roles in the reaction process, such as assisting the catalytic depolymerization of PET, catalyzing the in-situ reforming of ethylene glycol to produce hydrogen, inhibiting the methanation reaction of hydrogen / COx, inhibiting the deactivation of Ru-based catalysts, and optimizing the active sites of ruthenium metal, and cleverly combines the PET pure water phase hydrolysis process and the PET hydrolysis product liquid phase reforming process together, so that it produces hydrogen-rich synthesis gas and terephthalic acid in one pot. Due to the high specific surface area and porous structure of mesoporous carbon, it has excellent dispersibility under hydrothermal conditions, stimulates the catalytic activity of Ru and ZnO, and uses it as a catalyst carrier to reduce the amount of catalyst used.

[0008] Preferably, the reaction temperature used for the one-pot conversion of PET is 180-250°C and the reaction pressure is 1-3MPa. At this temperature, PET can undergo depolymerization in a pure water phase. In addition, ethylene glycol, as the main depolymerization product, can undergo in-situ reforming reaction within this temperature range. More preferably, the reaction temperature is 220-250°C and the reaction pressure is 2-3MPa. Compared with traditional supercritical hydrothermal reactions (temperature>374°C, pressure>22MPa) and steam reforming reactions (temperature>600°C), the hydrothermal environment of the reaction temperature of 180-250°C and the reaction pressure of 1-3MPa is relatively mild.

[0009] Preferably, the mass ratio of pure water, PET and catalyst is in the range of 2000:20:1 to 2000:20:5, and the mass ratio is calculated in proportion based on the masses of pure water, PET and catalyst.

[0010] The method for one-pot conversion of PET in a pure water phase system proposed by the present invention does not use any acid / alkali / organic solvent or other chemicals that are likely to cause harm to the ecological environment during the treatment of PET. Under the catalytic action of the catalyst, PET is completely converted into terephthalic acid and hydrogen-rich synthesis gas in one pot under mild hydrothermal conditions. The catalyst can play an auxiliary role in the process of hydrolyzing PET into terephthalic acid and ethylene glycol, and can also catalyze the in-situ reforming of ethylene glycol to produce hydrogen-rich synthesis gas.

[0011] The present invention also proposes a catalyst for one-pot conversion of PET in a pure water phase system, wherein the catalyst is a mesoporous carbon (MEC)-based ruthenium-zinc oxide multifunctional catalyst (xRu-yZnO / MEC). Preferably, the ruthenium loading in the catalyst accounts for 4 to 6% of the catalyst mass; the zinc oxide loading in the catalyst accounts for 5 to 15% of the catalyst mass.

[0012] More preferably, the ruthenium loading in the catalyst accounts for 4-5% of the catalyst mass. When the ruthenium loading is within the above range, the one-pot conversion process of PET in a pure water phase system is the best, the PET conversion rate is close to 100%, and the relative economy is higher. Too low ruthenium loading will result in insufficient metal active sites, resulting in poor catalytic effect, and too high ruthenium loading will increase operating costs.

[0013] More preferably, the loading amount of zinc oxide accounts for 5-10% of the mass of the catalyst. When the loading amount of zinc oxide is within the above range, it has the best effect on the one-pot conversion process of PET in a pure water phase system, and the PET conversion rate is close to 100%. Zinc oxide, as a promoter, can not only improve the catalytic activity of the catalyst by increasing the dispersion of ruthenium active metal on the mesoporous carbon carrier, but also has an auxiliary effect on the cleavage of ester bonds in PET during the hydrolysis of PET. However, too high a loading amount of zinc oxide will cause a serious decrease in the specific surface area and pore volume of the catalyst, thereby reducing the activity of the catalyst. Too low a loading amount of zinc oxide will not have sufficient catalytic effect on the catalyst. Therefore, the loading amount of zinc oxide plays a key role in optimizing the activity of the catalyst.

[0014] The present invention also proposes a method for preparing the catalyst for one-pot conversion of PET in a pure water phase system, comprising the following steps:

[0015] S1. dissolving the zinc salt in solvent A, then adding mesoporous carbon, stirring the obtained catalyst sample at room temperature for a certain period of time to allow the zinc salt to be impregnated into the mesoporous carbon support, then uniformly stirring at a certain temperature until the water in the catalyst sample is completely volatilized, and then drying and calcining to obtain a mesoporous carbon-based zinc oxide catalyst support;

[0016] S2. The ruthenium salt is dissolved in solvent B, and then the mesoporous carbon-based zinc oxide catalyst carrier obtained in step S1 is added, and the obtained catalyst sample is stirred at room temperature for a certain period of time to allow the ruthenium salt to be impregnated into the mesoporous carbon-based zinc oxide catalyst carrier, and then uniformly stirred at a certain temperature until the moisture of the catalyst sample is completely evaporated, and then dried, calcined and reduced to obtain a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst.

[0017] Preferably, the zinc salt and ruthenium salt are both soluble salts.

[0018] Preferably, the zinc salt includes any one or more of zinc nitrate, zinc acetate and zinc chloride.

[0019] Preferably, the ruthenium salt is ruthenium chloride or ruthenium nitrosyl nitrate.

[0020] Preferably, the specific surface area of ​​the mesoporous carbon is 900 to 1100 m 2 / g, pore diameter is 3-5nm, pore volume is 1-3cm 3 / g.

[0021] Preferably, the solvent A and the solvent B used for dissolving the zinc salt and the ruthenium salt can be any one or more of water, methanol, ethanol, and isopropanol. Preferably, the solvent is deionized water, which is cheap and has good solubility. The solvents in step S1 and step S2 are the same.

[0022] Preferably, the added amount of the solvent is 20 times the total mass of the soluble salt and the mesoporous carbon.

[0023] Preferably, in step S1, the mixture is first stirred at room temperature for 10 to 24 hours until the zinc salt is fully impregnated into the mesoporous carbon support to form a uniform solid-liquid mixture, and then stirred at a temperature of 50 to 90° C. until the water in the catalyst sample is completely volatilized. More preferably, the mixture is stirred at a temperature of 70 to 80° C. for 12 to 15 hours until the water in the catalyst sample is completely volatilized.

[0024] Preferably, in step S2, the mixture is first stirred at room temperature for 10 to 24 hours until the ruthenium salt is fully impregnated into the mesoporous carbon support to form a uniform solid-liquid mixture, and then stirred at a temperature of 70 to 90° C. until the water in the catalyst sample is completely volatilized. More preferably, the mixture is stirred at a temperature of 80° C. for 12 to 15 hours until the water in the catalyst sample is completely volatilized.

[0025] Preferably, in step S1, the calcination temperature is 400-700°C and the calcination time is 3-7 hours. In order to prevent the entry of air and the combustion of the mesoporous carbon, nitrogen is used as the calcination atmosphere. More preferably, the calcination temperature is 500-600°C and the time is 3-4 hours, at which time the zinc salt can be almost completely decomposed into zinc oxide, and the zinc salt crystallization condition is better.

[0026] Preferably, in step S2, the calcination-reduction temperature is 200-500°C, and the calcination-reduction time is 2-6 hours. More preferably, 20% hydrogen + 80% argon is used as the calcination-reduction atmosphere, the calcination-reduction temperature is 400-450°C, and the time is 3-4 hours. In the calcination-reduction stage, the catalyst is both calcined and reduced in situ, and the ruthenium salt is completely decomposed and reduced by hydrogen to ruthenium metal element, thereby giving full play to the catalytic effect.

[0027] Beneficial effects of the present invention:

[0028] 1. The one-pot conversion process of PET in a pure water phase system proposed by the present invention converts PET into terephthalic acid chemicals and hydrogen-rich synthesis gas mainly containing hydrogen, carbon dioxide and methane in a pure water phase in an environment without any acid / alkali / organic solvent, wherein the concentration of hydrogen can be as high as 70%. The process reaction is simple and ingenious, the working conditions are mild, the reaction temperature does not exceed 250°C, and the reaction process does not produce any by-products such as tar and pollutants that have a negative impact on the environment. The process can achieve efficient and clean conversion of PET, and the produced terephthalic acid has high purity and is an important chemical synthesis raw material. It can be directly recycled and reused, and the produced hydrogen-rich synthesis gas is of great significance to alleviating the shortage of fossil energy.

[0029] 2. The present invention proposes a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst for a one-pot conversion process of PET in a pure water phase system. The preparation process is simple, the catalytic activity is high, and a conversion rate of PET close to 100% can be achieved. In addition, the catalyst has high stability and strong reusability.

[0030] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings.

Brief Description of the Drawings

[0031] Figure 1 This is a flow chart of a method for one-pot conversion of PET in a pure water phase system of the present invention;

[0032] Figure 2 It is a mechanism diagram of a method for one-pot conversion of PET in a pure water phase system of the present invention;

[0033] Figure 3are scanning electron microscope images of mesoporous carbon, Ru / MEC, and Ru-5ZnO / MEC before and after reaction;

[0034] Among them, (a) is a MEC carrier; (b) is a fresh Ru / MEC catalyst; (c) is a Ru / MEC catalyst after reaction; (d) is a fresh Ru-5ZnO / MEC catalyst; (e) is a Ru-5ZnO / MEC catalyst after reaction;

[0035] Figure 4 is the X-ray diffraction pattern (XRD spectrum) of Ru / MEC and xRu-yZnO / MEC;

[0036] Figure 5 is the X-ray photoelectron spectroscopy analysis diagram of xRu-yZnO / MEC (ZnO phase);

[0037] Figure 6 is the X-ray photoelectron spectroscopy analysis diagram of xRu-yZnO / MEC (Ru phase);

[0038] Figure 7 This is a high-resolution transmission electron microscope image of the xRu-yZnO / MEC catalyst;

[0039] Figure 8 It is a comparison chart of X-ray diffraction between terephthalic acid produced by the method of the present invention and commercial terephthalic acid;

[0040] Fig. 9 It is a Fourier transform infrared absorption spectrum comparison diagram of terephthalic acid produced by the method of the present invention and commercial terephthalic acid;

[0041] Fig.10 The nuclear magnetic resonance images of terephthalic acid and commercial terephthalic acid produced by the method of the present invention are shown in FIG. 1 , wherein (I) represents commercial terephthalic acid; (II) represents plastic lunch box waste; (III) represents colored waste beverage bottles; (IV) represents transparent waste plastic bottles; (V) represents polyester fiber waste; and (VI) represents mixed plastics containing the above-mentioned real waste plastics. [Specific implementation method]

[0042] In order to make the purpose, technical scheme and things of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0043] The invention discloses a method for one-pot conversion of PET in a pure water phase system. In the absence of acid / alkali / organic solvent, pure water, PET and catalyst (xRu-yZnO / MEC) are mixed and loaded into a hydrothermal reactor in a mass ratio of 2000:20:1 to 2000:20:5. Under the conditions of reaction temperature of 180 to 250°C and reaction pressure of 1 to 3MPa, PET is converted in one pot under a low temperature, low pressure and mild hydrothermal environment to obtain terephthalic acid chemicals and hydrogen-rich synthesis gas. The main components of the hydrogen-rich synthesis gas include hydrogen, carbon dioxide and methane, wherein the molar fraction of hydrogen can reach 70%, and the PET conversion rate is close to 100%.

[0044] The reaction pathway of the one-pot conversion of PET into hydrogen-rich syngas and terephthalic acid in pure water phase catalyzed by mesoporous carbon (MEC)-based ruthenium-zinc oxide multifunctional catalyst is as follows:

[0045] See also Figure 2In the first stage of the one-pot conversion process of PET, PET is first converted into intermediate products such as PET-oligomers and bis(hydroxyethyl)terephthalate. The hydrothermal temperature of 220-250°C is conducive to promoting the hydrolysis of the CO ester bond in PET. Since the mesoporous carbon carrier has a strong adsorption capacity, the intermediate products obtained by the hydrolysis of PET will be adsorbed on the surface of the mesoporous carbon carrier in a small amount, covering part of the ruthenium metal active sites, thereby causing the deactivation of the catalyst. There is a strong interaction between the C=O bond in the intermediate products such as PET-oligomers and bis(hydroxyethyl)terephthalate and the zinc oxide metal cation in the xRu-yZnO / MEC catalyst, making the carbon cation more positively charged, thereby promoting the adsorption of oxygen in water on the carbon of the CO bond. Subsequently, the protons of water will attack the oxygen on the CO ester bond, resulting in the rupture of the CO ester bond. Therefore, under the combined catalysis of the hydrothermal medium and the ZnO active sites on the xRu-yZnO / MEC catalyst, the intermediate products such as PET-oligomers and bis(hydroxyethyl)terephthalate are further hydrolyzed into terephthalic acid and ethylene glycol monomers, thereby inhibiting the catalyst deactivation. In the second stage of the one-pot conversion process of PET, due to the good dispersibility and strong adsorption capacity of the mesoporous carbon with a high specific surface area under hydrothermal conditions, the ruthenium metal phase active sites supported on the mesoporous carbon can fully contact with the ethylene glycol produced in the first stage, and the ruthenium active metal in the xRu-yZnO / MEC catalyst has a high catalytic activity for the cleavage of the CC bond of ethylene glycol, promoting the water steam reforming reaction and the water gas reaction in the process of in-situ liquid phase reforming of ethylene glycol to produce hydrogen. In addition, as one of the main side reactions, the methanation reaction consumes hydrogen and carbon dioxide / carbon monoxide to produce methane. The ZnO in the xRu-yZnO / MEC catalyst has the effect of inhibiting the formation of methane, which to some extent offsets the catalytic effect of the ruthenium active metal on methanation, thereby increasing the hydrogen concentration in the synthesis gas product. In addition, the production of ethanol and acetic acid by cracking and rearrangement of CO on the active metal catalyst is also one of the main reasons for producing more synthesis gas (hydrogen, carbon dioxide, methane, ethane, etc.).

[0046] See also Figure 3, by scanning electron microscope analysis of Ru / MEC and xRu-yZnO / MEC catalysts before and after the one-pot conversion of PET, the C / O ratio on the surface of the Ru / MEC catalyst after the reaction in (c) was significantly increased compared with the fresh MEC carrier in (a) and the Ru / MEC catalyst in (b), while the C / O ratio on the surface of the xRu-yZnO / MEC catalyst after the reaction in (e) did not change significantly compared with the fresh Ru-5ZnO / MEC catalyst in (d), indicating that organic impurities with high C / O ratios were adsorbed on the surface of the Ru / MEC catalyst, thereby increasing the C / O ratio on the surface of the Ru / MEC catalyst. According to the experimental results, the hydrogen yield and PET conversion rate in the presence of the Ru / MEC catalyst were lower than those in the presence of the xRu-yZnO / MEC catalyst. Therefore, it can be inferred that in the absence of ZnO loading, the Ru / MEC catalyst also has a strong adsorption for the intermediate products such as PET-oligomers and bis(hydroxyethyl)terephthalate produced in the depolymerization reaction of PET, thereby increasing the C / O ratio on the surface of the Ru / MEC catalyst. The intermediate products adsorbed on the surface of mesoporous carbon will cover part of the ruthenium metal active sites, resulting in a significant decrease in the catalytic activity of the Ru / MEC catalyst. Compared with the Ru / MEC catalyst, the ZnO loaded on the xRu-yZnO / MEC catalyst can catalyze the further hydrolysis of the PET depolymerization intermediate products adsorbed on the surface of mesoporous carbon into terephthalic acid and ethylene glycol monomers, thereby eliminating the negative impact of the adsorbed intermediate products on the catalyst activity and avoiding serious deactivation of the catalyst. In addition, through CO-pulse tests on Ru / MEC and xRu-yZnO / MEC catalysts, it can be seen that the loading of ZnO significantly improves the dispersion of ruthenium active metal on mesoporous carbon, thereby improving the activity of ruthenium-based catalysts. Therefore, in the one-pot conversion process of PET, the xRu-yZnO / MEC catalyst plays multiple roles, including assisting the catalytic depolymerization of PET, catalyzing the in-situ reforming of ethylene glycol to produce hydrogen, inhibiting the methanation reaction of hydrogen / COx, inhibiting the deactivation of ruthenium-based catalysts, and optimizing the active sites of ruthenium metal.

[0047] The present invention also discloses a catalyst for the one-pot conversion method of PET in the above-mentioned pure water phase system. The catalyst is a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (xRu-yZnO / MEC), wherein x in the catalyst represents the loading amount of ruthenium, and the loading amount of ruthenium accounts for 1-6% of the mass of the catalyst; and y in the catalyst represents the loading amount of zinc oxide, and the loading amount of zinc oxide accounts for 3-20% of the mass of the catalyst.

[0048] Furthermore, the loading amount of ruthenium in the catalyst accounts for 4-6% of the mass of the catalyst; and the loading amount of zinc oxide in the catalyst accounts for 5-15% of the mass of the catalyst.

[0049] The present invention also discloses a method for preparing the above catalyst (xRu-yZnO / MEC), comprising the following steps:

[0050] S1. Dissolve the zinc salt in solvent A, then add mesoporous carbon, and continuously and uniformly stir the catalyst sample at room temperature for 10 to 24 hours until the zinc salt is fully impregnated into the mesoporous carbon carrier, then continue to uniformly stir the catalyst sample at a temperature of 50 to 90° C. until the moisture of the catalyst sample is completely volatilized, and then dry and calcine to obtain a mesoporous carbon-based zinc oxide catalyst carrier; wherein the calcination temperature is 400 to 700° C., the calcination time is 3 to 7 hours, and nitrogen is used as the calcination atmosphere;

[0051] S2. The ruthenium salt is dissolved in solvent B, and then the mesoporous carbon-based zinc oxide catalyst carrier obtained in step S1 is added, and the catalyst sample is continuously and uniformly stirred at room temperature for 10 to 24 hours until the ruthenium salt is fully impregnated into the mesoporous carbon-based zinc oxide catalyst carrier, and then the catalyst sample is continued to be uniformly stirred at a temperature of 80°C until the moisture of the catalyst sample is completely volatilized, and then dried, calcined and reduced to obtain a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst; wherein the calcination-reduction temperature is 200 to 500°C, the calcination-reduction time is 2 to 6 hours, and 20% hydrogen + 80% argon is used as the calcination-reduction atmosphere.

[0052] Furthermore, the zinc salt includes any one or more of zinc nitrate, zinc acetate, and zinc chloride. The ruthenium salt is ruthenium chloride. The specific surface area of ​​the mesoporous carbon is 900 to 1100 m 2 / g, pore diameter is 3-5nm, pore volume is 1-3cm 3 / g. The solvent A and the solvent B used to dissolve the zinc salt and the ruthenium salt can be any one or more of water, methanol, ethanol, and isopropanol.

[0053] See also Figure 4 According to the X-ray diffraction characterization of Ru / MEC and xRu-yZnO / MEC, it can be seen that the XRD spectrum of xZnO / MEC shows obvious diffraction peaks of ZnO at 31.7°, 34.3°, 36.2°, 47.4°, 56.5°, 62.8°, 67.8° and 69.1° at 2θ, corresponding to (100), (002), (101), (102), (110), (103), (112) and (201) crystal planes (JCPDC 36-1451). As the ZnO doping amount increases, the diffraction intensity of ZnO becomes stronger. These results indicate that ZnO has good crystallinity on the surface of the mesoporous carbon support. Importantly, Ru has no obvious diffraction peaks, which indicates that the Ru metal particles on the catalyst prepared by the present invention have ultra-small particle size and are well dispersed on the mesoporous carbon support.

[0054] See also Figure 7 To further confirm the above results, it can be seen from high-resolution transmission electron microscopy that the size of Ru metal particles is much smaller than that of ZnO, and the particle size is basically less than 10nm, and most of the Ru metal is dispersed in the form of ultrafine particles, which is consistent with the X-ray diffraction characterization results. In addition, there is no connection between the Ru metal particles and the ZnO particles, indicating that no alloy is formed between the two and no obvious interaction is produced. In addition, the results show that the lattice distances of metal Ru and ZnO are 0.208nm and 0.245nm, respectively, corresponding to the (101) crystal planes of metal Ru and ZnO, respectively. Because Ru and ZnO in the catalyst prepared by the present invention each play different catalytic roles, reducing the interaction between the two can avoid the reduction of catalytic activity.

[0055] See also Figure 5 and Figure 6 The chemical state of the xRu-yZnO / MEC catalyst was characterized by X-ray photoelectron spectroscopy. 2+ (Zn 2p 1 / 2) and Zn 2+ (Zn 2p 3 / 2 The binding energies of Ru(0)3d are 1044.8eV and 1021.8eV respectively. The Ru peaks at 280.7eV and 285.4eV are Ru(0)3d 5 / 2 and Ru(0)3d 3 / 2 The CO-pulse test of Ru / MEC and Ru-5ZnO / MEC catalysts showed that the dispersion of ruthenium active metal in Ru / MEC was 21.84%, while the dispersion of ruthenium active metal in Ru-5ZnO / MEC was 23.87%, which indicates that the loading of ZnO significantly improves the dispersion of ruthenium active metal on mesoporous carbon, thereby improving the activity of ruthenium-based catalysts.

[0056] Example 1

[0057] Catalyst preparation process:

[0058] Step (1): Dissolve 0.119 g of zinc nitrate hexahydrate in 20 g of deionized water, add 1 g of mesoporous carbon to the mixed solution, and stir the catalyst sample evenly and continuously at room temperature for 12 hours until the zinc salt is fully impregnated into the mesoporous carbon carrier, and then continue to stir the catalyst sample evenly at a temperature of 80°C until the water in the catalyst sample is completely volatilized. Then move the solid catalyst sample to a 105°C oven for 12 hours of drying. The dried catalyst sample is calcined at 500°C for 4 hours in a nitrogen atmosphere, and after cooling, a mesoporous carbon-based zinc oxide catalyst carrier (3ZnO / MEC) with a zinc oxide loading of 3% is obtained.

[0059] Step (2): 0.0756g of anhydrous ruthenium chloride is dissolved in 15g of deionized water, 0.7g of a mesoporous carbon-based zinc oxide catalyst carrier is added to the mixed solution, and the catalyst sample is continuously and uniformly stirred at room temperature for 12 hours until the ruthenium salt is fully impregnated into the mesoporous carbon-based zinc oxide catalyst carrier, and then the catalyst sample is continued to be uniformly stirred at a temperature of 80°C until the water in the catalyst sample is completely volatilized. The solid catalyst sample is then transferred to a 105°C oven for 12 hours of drying. The dried catalyst sample is calcined-reduced at 450°C for 3 hours in an atmosphere of 20% hydrogen-80% argon, and after cooling, a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-3ZnO / MEC) with a zinc oxide loading of 3% and a ruthenium loading of 5% is obtained.

[0060] One-pot conversion process of PET in pure water system:

[0061] 0.7g PET powder, 70ml deionized water, and 0.14g 5Ru-3ZnO / MEC catalyst were added to the hydrothermal reactor, and the temperature was raised to 240°C at a heating rate of 5% / min and maintained for 120min. After the reaction, the reactor temperature was quickly cooled to room temperature by air cooling + water cooling, and then the hydrogen-rich synthesis gas was collected by air bags. The solid and liquid were separated by a filter, and the obtained solid was transferred to a 105°C oven for 12 hours of drying. The obtained solid was a mixture of terephthalic acid and the catalyst. Due to the difference in particle size between terephthalic acid and the catalyst used, a screening device was used to separate the two to obtain high-purity terephthalic acid.

[0062] Example 2

[0063] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.203 g, and a mesoporous carbon-based zinc oxide catalyst carrier (5ZnO / MEC) with a zinc oxide loading of 5% was obtained, and the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-5ZnO / MEC) with a zinc oxide loading of 5% and a ruthenium loading of 5%.

[0064] The one-pot conversion process of PET in pure water phase system adopts the same method as that in Example 1, except that 5Ru-5ZnO / MEC catalyst is used.

[0065] Example 3

[0066] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.429 g, and a mesoporous carbon-based zinc oxide catalyst carrier (10ZnO / MEC) with a zinc oxide loading of 10% was obtained, and the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-10ZnO / MEC) with a zinc oxide loading of 10% and a ruthenium loading of 5%.

[0067] The one-pot conversion process of PET in pure water phase system adopts the same method as Example 1, except that 5Ru-10ZnO / MEC catalyst is used.

[0068] Example 4

[0069] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.685 g, and a mesoporous carbon-based zinc oxide catalyst carrier (15ZnO / MEC) with a zinc oxide loading of 15% was obtained, and the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-15ZnO / MEC) with a zinc oxide loading of 15% and a ruthenium loading of 5%.

[0070] The one-pot conversion process of PET in pure water phase system adopts the same method as that in Example 1, except that 5Ru-15ZnO / MEC catalyst is used.

[0071] Example 5

[0072] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.975 g, and a mesoporous carbon-based zinc oxide catalyst carrier (20ZnO / MEC) with a zinc oxide loading of 20% was obtained; the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-20ZnO / MEC) with a zinc oxide loading of 20% and a ruthenium loading of 5%.

[0073] The one-pot conversion process of PET in pure water phase system adopts the same method as Example 1, except that 5Ru-20ZnO / MEC catalyst is used.

[0074] Example 6

[0075] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.975 g, and a mesoporous carbon-based zinc oxide catalyst carrier (20ZnO / MEC) with a zinc oxide loading of 20% was obtained; the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-20ZnO / MEC) with a zinc oxide loading of 20% and a ruthenium loading of 5%.

[0076] The one-pot conversion process of PET in pure water phase system adopts the same method as Example 1, except that 5Ru-25ZnO / MEC catalyst is used.

[0077] Example 7

[0078] The catalyst was prepared by the same preparation method as in Example 1, except that: the mass of zinc nitrate hexahydrate in step (1) was 0.975 g, and a mesoporous carbon-based zinc oxide catalyst carrier (20ZnO / MEC) with a zinc oxide loading of 20% was obtained; the product obtained in step (2) was a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst (5Ru-20ZnO / MEC) with a zinc oxide loading of 20% and a ruthenium loading of 5%.

[0079] The one-pot conversion process of PET in a pure water phase system adopts the same method as in Example 1, except that 5Ru-30ZnO / MEC catalyst is used.

[0080] The results of Examples 1-7 show that when the ZnO loading is 5%, that is, when the catalyst is 5Ru-5ZnO / MEC, the catalytic effect of the catalyst is optimal. Continuing to increase the ZnO loading, especially when the ZnO loading exceeds 15%, will reduce the specific surface area of ​​the catalyst, affect the dispersion of Ru metal, and thus reduce the catalytic activity of the catalyst.

[0081] Example 8 (Comparative Example)

[0082] 0.0756g of anhydrous ruthenium chloride was dissolved in 15g of deionized water, 0.7g of mesoporous carbon was added to the mixed solution, and the catalyst sample was continuously and uniformly stirred at room temperature for 12 hours until the ruthenium salt was fully impregnated into the mesoporous carbon carrier, and then the catalyst sample was continued to be uniformly stirred at a temperature of 80°C until the water in the catalyst sample was completely volatilized. The solid catalyst sample was then transferred to a 105°C oven for 12 hours of drying. The dried catalyst sample was calcined-reduced at 450°C for 3 hours in an atmosphere of 20% hydrogen-80% argon, and after cooling, a mesoporous carbon-based ruthenium catalyst (5Ru / MEC) with a ruthenium loading of 5% was obtained. The one-pot conversion process of PET in a pure water phase system adopts the same method as in Example 1.

[0083] The one-pot conversion process of PET in pure water phase system adopts the same method as that in Example 1, except that 5Ru / MEC catalyst is used.

[0084] Examples 9 to 12

[0085] The catalyst was prepared using the same method as in Example 2.

[0086] The one-pot conversion process of PET in pure water phase system adopts the same method as that in Example 1. The difference is that in Examples 7 to 10, the reaction temperatures of the conversion in the hydrothermal reactor are 210° C., 220° C., 230° C. and 250° C. respectively.

[0087] Embodiments 13 to 16

[0088] The catalyst was prepared using the same method as in Example 2.

[0089] The one-pot conversion process of PET in pure water phase system adopts the same method as that in Example 12. The difference is that the reaction time of the conversion in the hydrothermal reactor in Examples 11 to 14 is 30 min, 60 min, 90 min and 150 min respectively.

[0090] Examples 17 to 20

[0091] The catalyst was prepared using the same method as in Example 2.

[0092] The one-pot conversion process of PET in pure water phase system adopts the same method as Example 12. The difference is that the catalyst loading amounts in Examples 15 to 18 are 0.035 g, 0.07 g, 0.105 g and 0.175 g, respectively.

[0093] Examples 21-22

[0094] The catalyst was prepared by the same method as in Example 2. The difference was that the loading amounts of anhydrous ruthenium chloride in Examples 21 and 22 were 0.013 g and 0.08 g, respectively, and the obtained catalysts were recorded as 1Ru-5ZnO / MEC and 6Ru-5ZnO / MEC, respectively.

[0095] The one-pot conversion process of PET in a pure water phase system adopts the same method as Example 12, except that Examples 21 to 22 use 4Ru-5ZnO / MEC and 6Ru-5ZnO / MEC catalysts, respectively.

[0096] Table 1 Results of one-step catalytic conversion of PET in pure water phase system in Examples 1 to 22

[0097]

[0098]

[0099] Embodiments 23 to 27

[0100] The catalyst was prepared using the same method as in Example 2.

[0101] The one-pot conversion process of PET in a pure water phase system adopts the same method as that of Example 12. The difference is that the raw materials used in Examples 23 to 27 are respectively real colored waste beverage bottles, transparent waste plastic bottles, polyester fiber waste, plastic lunch box waste, and mixed plastics containing the above real waste plastics.

[0102] Table 2 One-step catalytic conversion process results of different types of real PET in pure water phase system in Examples 23-27

[0103]

[0104] The terephthalic acid produced during the one-pot conversion of various real PET wastes was characterized and compared with terephthalic acid standards.

[0105] See also Figure 8 The obtained X-ray diffraction spectrum of terephthalic acid showed strong diffraction peaks at 17.3°, 27.8°, 29.5°, 31.7° and 39.6°, corresponding to the terephthalic acid standard.

[0106] See also Fig. 9 The functional groups in the obtained terephthalic acid were determined by Fourier transform infrared absorption spectroscopy. -1 and 1284.5cm -1 The peak at 1571.9 cm-1 can be attributed to the C=O and CO bonds in terephthalic acid. -1 and 1510.2cm -1 The vibration of the benzene ring skeleton was observed at the peak of .

[0107] See also Fig.10 The chemical structure and purity of the obtained terephthalic acid were further analyzed by nuclear magnetic resonance. 13 The peaks observed at 129.8 ppm, 134.8 ppm and 167.1 ppm in the CNMR spectrum are respectively attributed to the aromatic carbon, quaternary aromatic carbon and carbonyl carbon of terephthalic acid. 1 In H NMR, the weak peaks at 8.1ppm and 13.3ppm correspond to the aromatic protons and carboxyl protons of terephthalic acid, respectively. Importantly, the X-ray diffraction spectra, Fourier transform infrared absorption spectra and nuclear magnetic resonance spectra of all prepared terephthalic acids are basically consistent with those of terephthalic acid standards, and no obvious impurity peaks are found, indicating that the prepared terephthalic acid has a high purity.

[0108] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Any solution that is a simple transformation of the present invention belongs to the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system, characterized in that: The following steps are involved: S1. dissolving a zinc salt in solvent A, then adding mesoporous carbon, stirring the obtained catalyst sample at room temperature for a certain period of time to allow the zinc salt to be impregnated into the mesoporous carbon support, and then stirring at a certain temperature until the water in the catalyst sample is completely volatilized, and then drying and calcining to obtain a mesoporous carbon-based zinc oxide catalyst support; S2. The ruthenium salt is dissolved in solvent B, and then the mesoporous carbon-based zinc oxide catalyst carrier obtained in step S1 is added, and the obtained catalyst sample is stirred at room temperature for a certain period of time to allow the ruthenium salt to be impregnated into the mesoporous carbon-based zinc oxide catalyst carrier, and then stirred at a certain temperature until the moisture of the catalyst sample is completely evaporated, and then dried, calcined and reduced to obtain a mesoporous carbon-based ruthenium-zinc oxide multifunctional catalyst.

2. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S1, the zinc salt includes any one or more of zinc nitrate, zinc acetate, and zinc chloride.

3. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S2, the ruthenium salt is ruthenium chloride or ruthenium nitrosyl nitrate.

4. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S1, the specific surface area of ​​the mesoporous carbon is 900-1100 m 2 / g, pore diameter is 3~5nm, pore volume is 1~3cm 3 / g.

5. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: The solvent A and the solvent B are any one or more of water, methanol, ethanol and isopropanol.

6. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S1, the mixture is first stirred at room temperature for 10 to 24 hours until the zinc salt is fully impregnated into the mesoporous carbon support, and then stirred at a temperature of 50 to 90° C. until the water in the catalyst sample is completely volatilized.

7. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S2, the mixture is first stirred at room temperature for 10 to 24 hours until the ruthenium salt is fully impregnated into the mesoporous carbon support, and then stirred at a temperature of 70 to 90° C. until the water in the catalyst sample is completely volatilized.

8. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S1, the calcination temperature is 400-700° C., the calcination time is 3-7 hours, and nitrogen is used as the calcination atmosphere.

9. The method for preparing a catalyst for a one-pot conversion of PET in a pure water phase system as claimed in claim 1, characterized in that: In step S2, the calcination-reduction temperature is 200-500°C, the calcination-reduction time is 2-6 hours, and 20% hydrogen + 80% argon is used as the calcination-reduction atmosphere.

10. A catalyst, characterized in that: Prepared by any one of the preparation methods of claims 1 to 9.

11. The catalyst according to claim 10, characterized in that: The loading amount of ruthenium in the catalyst accounts for 4-6% of the mass of the catalyst; the loading amount of zinc oxide in the catalyst accounts for 5-15% of the mass of the catalyst.

12. A method for one-pot conversion of PET in a pure water phase system, characterized in that: In the absence of acid / alkali / organic solvent, pure water, PET and the catalyst prepared according to claim 10 are mixed in a certain proportion, and under certain reaction temperature and reaction pressure conditions, PET is converted in one pot to produce terephthalic acid chemicals and hydrogen-rich synthesis gas.

13. The method for one-pot conversion of PET in a pure water phase system as claimed in claim 12, characterized in that: The loading amount of ruthenium in the catalyst accounts for 1-6% of the mass of the catalyst, and the loading amount of zinc oxide in the catalyst accounts for 3-20% of the mass of the catalyst.

14. The method for one-pot conversion of PET in a pure water phase system as claimed in claim 12, characterized in that: The reaction temperature is 180-250° C., and the reaction pressure is 1-3 MPa.

15. The method for one-pot conversion of PET in a pure water phase system as claimed in claim 12, characterized in that: The mass ratio of the pure water, PET and catalyst is in the range of 2000:20:1 to 2000:20:5.

Citation Information

Patent Citations

  • Method of a high metal loading catalyst for preparing glycol from carbohydrate

    CN103420796A

  • Method of low metal loading catalyst for preparing glycol from carbohydrate

    CN103420797A